43.7k views
1 vote
A student solved z + (-0.72) = -2.5 for z using the

following steps.
Step 1: Z + (-0.72) + (-0.72) = -2.5+ (-0.72)
z = -2.5+ (-0.72)
Step 2:
Step 3:
z = -3.22
What was the student's error?

User Taraz
by
4.9k points

2 Answers

7 votes

Answer:

To solve, you must use the inverse operation. In step 1, -0.72 should have been subtracted from both sides, not added. Otherwise, 0.72 should have been added to both sides, not -0.72.

Explanation:

User Ahcox
by
5.5k points
6 votes

Answer:

  • Mistake in step1

Explanation:

Given

  • z + (-0.72) = -2.5

Solving in steps

  • 1. ⇒ z + (-0.72) - (-0.72) = -2.5 - (-0.72)
  • 2. ⇒ z = - (2.5 - 0.72)
  • 3. ⇒ z = - 1.78

The student's mistake was adding (-0.72) instead of - (-0.72) or 0.72

User Simon Munro
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.